Information flows’ movement analysis in the integrated accounting and analytical system of individual entrepreneurs in the web business on marketplaces sphere - T. M. Nepryahina (Вестник университета, 2023)
The annual increase in the number of individual entrepreneurs in comparison with the decrease in the number of legal entities, especially in the form of microbusiness in the field of online commerce on marketplaces, reflects the relevance of the chosen topic. The analysis of scientific articles over the past year confirms that research on the specifics of the individual entrepreneurs’ activities is aimed primarily at the external interaction of entrepreneurs and the state. The scope of internal control and the features of accounting for individual entrepreneurs have not been previously considered by scientists. Earlier in the works of scientists, business management processes, elements of a balanced scorecard system and stages of the accounting process were included for a simplified structure of an integrated accounting and analytical system. The study purpose is to optimize information flows in the accounting and analytical system of individual entrepreneurs in the field of web business on marketplaces. As a result of the study, the information movement has been clarified in order to fix indicators of strategic goals and the formation of tax accounting registers. The goals’ components and system’s objectives of balanced indicators for individual entrepreneurs have been formed, considering the specifics of web business on marketplaces. The tasks’ interrelation is reflected and the possible connection of universal indicators within the framework of strategic goals is described. These studies can be used as the development of state recommendations on accounting by individual entrepreneurs as an alternative to existing ones for organizations. Further studies may be devoted to assessing the effectiveness of the accounting and analytical system for individual entrepreneurs and clarifying the algorithm of automation, as well as obtaining information when accounting within such a system.